Effect of reactor configuration in the acidogenic fermentation profile - Runa, Viviane Marisa Reis (2016)
Polyhydroxyalkanoates (PHA) emerge as a promising alternative to the conventional plastics due to its biodegradability, biocompatibility and thermochemical properties. Several strategies have been studied in order to decrease PHA production costs and enlarge their commercialization, such as the use of pre-treated renewable substrates and the development of economically and environmentally sustainable extraction procedures. The first part of this work aimed to compare two different reactor operation modes for the production of short-chain organic acids (SCOA), preferred substrates for polyhydroxyalkanoates (PHA) production. Acidogenic fermentation was performed by mixed microbial cultures (MMC) in a continuously stirred tank reactor (CSTR) and in a sequential batch reactor (SBR) operated for 130 days and submitted to the same operational conditions. Both reactors achieved full fermentation (>90%) for an OLR of 10gCOD/L·d, with a different range and relative concentrations of fermentation products (FP). Ethanol (EtOH) was the dominant FP in the CSTR and acetic acid (HAc) the main SCOA produced, while the SBR presented butyric acid (HBu) as dominant FP, slightly higher than the HAc concentration. Although the CSTR showed a higher yield of SCOA than the SBR – 0.671 and 0.604, respectively -, the SBR presented a higher conversion of substrate into SCOA – 48% over 38%. The second part of the work focused on the PHA extraction from pure cultures of C. necator and MMC with surfactants and an enzymatic solution from the hydrolysate of the fungus P. variotii. An extraction protocol was developed for application of the extractive agents studied. Afterwards, a systematic extraction of PHA from the microbial cultures was performed and several concentrations and temperatures tested. Among the surfactants used, BRIJ 30 presented the most promising results with recoveries above 30% for the pure cultures and above 20% for the MMC. The enzymatic solution enabled the PHA extraction when used at a concentration of 10% but not in inferior percentages, indicating that application of higher concentrations should be studied.